2017
DOI: 10.1016/j.jenvman.2017.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Clogging in permeable concrete: A review

Abstract: Permeable concrete (or "pervious concrete" in North America) is used to reduce local flooding in urban areas and is an important sustainable urban drainage system. However, permeable concrete exhibits reduction in permeability due to clogging by particulates, which severely limits service life. This paper reviews the clogging mechanism and current mitigating strategies in order to inform future research needs. The pore structure of permeable concrete and characteristics of flowing particulates influence cloggi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
90
0
22

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 198 publications
(123 citation statements)
references
References 47 publications
11
90
0
22
Order By: Relevance
“…This property is directly related to the particle size distribution and the consumption of materials. Table 4 lists a summary of the mechanical and hydraulic properties According to Table 4, the coefficients of variation found for the properties evaluated are in accordance with the literature [31], due to the quality control during the casting of the specimens, once all concretes were cast on the same day, reducing the temperature interference. In addition, moisture control of the aggregates was performed and, because the compacting procedure was performed with the help of the vibrating table, there was a reduction in the variability resulting from the human operator in the production process.…”
Section: Hydraulic Propertiessupporting
confidence: 78%
“…This property is directly related to the particle size distribution and the consumption of materials. Table 4 lists a summary of the mechanical and hydraulic properties According to Table 4, the coefficients of variation found for the properties evaluated are in accordance with the literature [31], due to the quality control during the casting of the specimens, once all concretes were cast on the same day, reducing the temperature interference. In addition, moisture control of the aggregates was performed and, because the compacting procedure was performed with the help of the vibrating table, there was a reduction in the variability resulting from the human operator in the production process.…”
Section: Hydraulic Propertiessupporting
confidence: 78%
“…Solving the problem of clogging will make porous concrete more efficient, resilient, and cost effective, thereby promoting wider use. However, the study also found that existing maintenance methods for porous concrete, such as vacuum sweeping and pressure washing, had questionable effectiveness [40].…”
Section: Maintenancementioning
confidence: 89%
“…In a study on porous concrete [40], it was shown how the pore network is highly complex and heterogeneous. In addition, the pore channels under the pavement are tortuous, with variable cross-sections and random interconnectivity.…”
Section: Maintenancementioning
confidence: 99%
“…A comprehensive review was recently presented (Kia et al, 2017). Some studies have observed that clogging usually occurs on the surface or in the upper layer of the permeable pavement (Kayhanian et al 2012, Yong et al 2013, while others found that sediments are likely to clog within the permeable concrete or underlying soil (Chopra et al, 2010;Mata and Leming, 2012;Lucke and Beecham, 2011).…”
Section: Introductionmentioning
confidence: 99%